Floristic Diversity And Conservation Importance of Bukit Bauk (Terengganu) in Peninsular Malaysia - Tam, Sheh May (1998)
Bukit Bauk is an isolated, coastal small hilly range which is part of the Terengganu hills situated in the low hills at the southern end of the East Range in the east coast of Terengganu in Peninsular Malaysia. These hills have been deemed to be extremely interesting botanically because they were surmissed to contain a high number of species and endemic plant'). However to date, a satisfactory inventory of plant species in the east coast have yet to be taken (are under-collected) and studied botanically. This study was therefore carried out to determine the floristic diversity of Bukit Bauk and subsequently compile a floristic checklist by checking relevant literature and through fieldwork; to assess the conservation importance of Bukit Bauk; to evaluate the conservation status of important species, where sampling plots and size were site and species specific and to determine threats to the flora of Bukit Bauk. The flora of Bukit Bauk was found to comprise 638 species (7.7% of the total flora of the Malay Peninsula) belonging to 285 genera and 103 families. Of these, 14.3% were endemic taxa (91 taxa) which constituted about 3.6% of the total number of endemic species in the Malay Peninsula. Bukit Bauk also contained 17.6% of the total number of tree species and 8.0% of endemic tree species in Peninsular Malaysia. The most speciose families on Bukit Bauk were Euphorbiaceae (59 species), Dipterocarpaceae (43 species), Rubiaceae (36 species) Palmae and Guttiferae (31 species respectively). Several specific types of vegetation could be distinguished on Bukit Bauk and it'> nearby lowland forest according to habitat, altitude zonation and floristic composition. The vegetation types were lowland dipterocarp forest (flatland, foothills and valley bottoms), vegetation on the seaward front, hill dipterocarp forest (steep slopes and hill ridges), vegetation on the summit, vegetation of disturbed areas and peat swamp forest. A total of 385 species (60.3%) of species found on Bukit Bauk provide one or more usage to humankind with 58.7% contributing more than one type of usage. Edible wild plants, products and medicinal plants are important to the local community in Terengganu.